The role of marketing information system in decision-making catalog In the production of pharmaceutical companies to contribute to Jordan’s General - عبد الباسط إبراهيم حسونة; بدر عايد القعيد; ونس الهنداوي; مرزوك عايد القعيد (Iraqi Journal for Administrative Sciences, 2024)
This study aims at reveal the relationship between the major components of marketing information system, and decision-making in Jordanian shareholding medicines production companies. It also aimed at introduce the concept, elements, and components of marketing information system. The data required for this study has been gained from two sources: the first is represented in the books, studies and previous research, while the second was field study. All Jordanian shareholding medicines production companies registered in Amman financial market were surveyed. The number of these was (7). For the purpose of this study a pre-designed questionnaire has been distributed on marketing managers, and the marketing information system staff working in these companies. At the end of this study, the researcher reached the following results: There is a statistically significant relation between each of the following marketing information system components, and decision-making: internal records, marketing research, and marketing intelligence. There is no specialized organizational unit for marketing information system in five of the seven companies under study. There is a weakness in the appointment of appropriate, qualified, and specialized staff who have the ability to do the work required by the marketing information system in Jordanian shareholding medicines production companies properly